Legal Certainty of Songwriters' Economic Rights in Music Royalty Management in Indonesia - Anggraeni, Happy Yulia; Tobing, Rismanto L.; Iskandar, Dedi (Research Horizon, 2025)
An urgent legal issue emerges from the normative disharmony between Article 9(2) and Article 23(5) of Law No. 28 of 2014 concerning Copyright. Article 9(2) requires creators to give written permission for the use of their works, implying a direct licensing mechanism, while Article 23(5) mandates the use of a collective management system through the National Collective Management Organization. This inconsistency has led to legal uncertainty, especially in the context of public performance royalties, and has disadvantaged songwriters due to a lack of transparency in royalty calculations. This study aims to examine the legal certainty of public performance licensing in Indonesia's music royalty management system by analyzing the implementation of Article 23(5) of Law No. 28 of 2014 and Government Regulation No. 56 of 2021. This study, using a normative juridical method, finds that despite Government Regulation No. 56 of 2021 establishing SILM and LMKN, licensing conflicts persist. It recommends harmonizing the regulation by clearly recognizing direct licensing under Article 9(2) while protecting moral rights under Article 5 of Law No. 28 of 2014.